Urea Facilitates the Translocation of Single-Stranded DNA and RNA Through the α-Hemolysin Nanopore - Japrung, Deanpen (The Biophysical Society, 2010)
The staphylococcal α-hemolysin (αHL) protein nanopore is under investigation as a fast, cheap detector for nucleic acid analysis and sequencing. Although discrimination of all four bases of DNA by the αHL pore has been demonstrated, analysis of single-stranded DNAs and RNAs containing secondary structure mediated by basepairing is prevented because these nucleic acids cannot be translocated through the pore. Here, we show that a structured 95-nucleotide single-stranded DNA and its RNA equivalent are translocated through the αHL pore in the presence of 4 M urea, a concentration that denatures the secondary structure of the polynucleotides. The αHL pore is functional even in 7 M urea, and therefore it is easily stable enough for analyses of challenging DNA and RNA species.